Recyclable magnetite-loaded palm shell-waste based activated carbon for the effective removal of methylene blue from aqueous solution - Wong, K.T. (Elsevier, 2016)
Magnetized palm shell-waste based activated carbon (MPBAC) was prepared using a simple impregnation of magnetite into palm shell-waste based activated carbon (PBAC) and used for the removal of methylene blue (MB) from an aqueous solution. Based on the isotherm results, MPBAC with the smallest particle size had the highest maximum adsorption capacity (Qmax = 163.3 mg g−1). Overall, the kinetic rates of MPBACs were slower than pristine PBACs due to the deposition of magnetite mostly on the outer surface. However, MB was electrostatically attracted towards the magnetite existing at the inner-pores and eventually adsorbed on the interface between the magnetite and the hydrophobic pore surface leading to high sorption density. The thermal regeneration indicated the removal capacities of MB by MPBAC were steady and higher than PBAC for repeated sorption. Through interpretation of thermogravimetric analysis and differential scanning calorimetry, the desorption energy of MB was lowered by the magnetite, leading to better regeneration ability for MPBAC.